Clarifying maritime criminal cases jurisdiction and its international implications - current legal developments in China - Chang, Yen-Chiang (Crime, law and social change, 2022)
On 20 February 2020, the Supreme People’s Court, the Supreme People’s Procuratorate and the China Coast Guard jointly issued the Notice on Issues concerning Jurisdiction of Maritime Criminal Cases (hereinafter the "Notice"). The Notice aims to ensure the effective performance of maritime right-safeguarding and law enforcement functions by the coast guard agencies, punishing maritime crimes by the law and protecting the State’s sovereignty, security, maritime rights and interests, as well as maritime order. Maritime criminal cases have strong international implications and their jurisdiction is subject to this short discussion. It is observed that by clarifying maritime criminal cases jurisdiction may to some extent reduce potential disputes in the context of law enforcement activities.